Measurement and mathematical modeling of hyperthermia induced bioeffects in pancreatic cancer cells - Chamani, Faraz (Kansas State University, 2023)
Surgical resection is the standard of care for pancreatic cancer, although treatment outcomes remain poor, and a large fraction of the patient population are not surgical candidates. Minimally invasive interventions employing non-ionizing energy, such as image-guided thermal ablation, are under investigation for treatment of unresectable tumors and potentially for debulking and downstaging tumors. Tissue regions at the periphery of an ablation zone are exposed to sub-ablative thermal profiles (referred to as “mild hyperthermia”), which may induce a range of bioeffects including change in perfusion, immune modulation, and others. Bioeffects induced by heating are a function of intensity of heating and duration of thermal exposure. This dissertation presents a suite of tools for integrated in vitro experimental studies and modeling for characterizing bioeffects following thermal exposure to pancreatic cancer cells. An instrumentation platform was developed for exposing monolayer cell cultures to temperatures in the range 42–50°C for 3–60 minutes. The platform was employed to determine the Arrhenius kinetic parameters of thermal injury to pancreatic cancer cells (i.e. loss in viability) following heating. When coupled with bioheat transfer models, these parameters facilitate investigations of thermal injury profiles in pancreatic tumors following thermal exposure with practical devices. There has been growing interest in exploring the potential of thermal therapies for modulating tumor—immune system interactions, due in part to release of damage associated molecular patterns (DAMPs) from stressed tumor cells and their role in recruiting and activating antigen presenting cells. The in vitro thermal exposure platform was further expanded to allow for experimental measurement of extracellular DAMPs released from murine pancreatic cancer cells following heating to temperatures in the range 42 – 50°C for 3-60 mins. A model predicting the dynamics of heat-induced DAMPs release was developed and may inform the design of experiments investigating the role of heat in modulating the anti-tumor immune response. While in vitro experiments on monolayers are informative, 3D cell cultures (e.g., spheroid, organoids) provide an experimental platform accommodating multiple cell types in an environment that may be more representative of tumors in vivo. Furthermore, while the water-bath based in vitro platform applied for monolayers is well suited to achieving near-uniform temperature profiles, in vivo delivery of hyperthermia often yields a gradient of temperatures that is not achieved through water-bath based heating. Thus, an in vitro platform for exposing cells in 3D culture (co-culture of multiple cell populations) to 2.45 GHz microwave hyperthermia was developed. The platform includes a printed patch antenna and associated thermal management elements and was applied to study changes in gene expression profile of a 3D culture of pancreatic cancer cells and fibroblasts. This non-contact microwave heating approach may help enable additional studies for exploring the bioeffects of heat on cancer cells.
Keywords: Hyperthermia; In vitro; Pancreatic cancer; Cell death; Arrhenius injury model; Thermal damage